2017
DOI: 10.21767/2472-1646.100025
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effect of Punicalagin against Ethanol-Induced Gastric Ulcer: The Possible Underlying Mechanisms

Abstract: Gastric ulcer is the most digestive disease found in clinical practice. Punicalagin (PCG) found in pomegranate juice has antioxidant and tissue repair properties. Therefore, the aim of this study was to investigate punicalagin's gastroprotective effect against ethanol-induce gastric injury. Four groups of rats; first group served as control, group 2: Treated with absolute ethanol (5 ml/kg, po), group 3: Rats were pre-treated with ranitidine (as a reference drug) (50 mg/kg, po) before ethanol and group 4: Pre-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
(38 reference statements)
5
11
0
Order By: Relevance
“…Pre-treatment with the plant extract decreased gastric acid secretions vs. stomach ulcer group. Therefore and in agreement with the present study, substances which suppress gastric acid secretion have the ability to accelerate the healing process of the gastric lesions and inhibit the formation of mucosal injury ( Brzozowski et al., 2000 ; Katary and Salahuddin, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…Pre-treatment with the plant extract decreased gastric acid secretions vs. stomach ulcer group. Therefore and in agreement with the present study, substances which suppress gastric acid secretion have the ability to accelerate the healing process of the gastric lesions and inhibit the formation of mucosal injury ( Brzozowski et al., 2000 ; Katary and Salahuddin, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…It has previously reported that acute exposure of ethanol decreased gastric juice pH as compared to the control group by increasing acid secretion. 40 Administration of absolute ethanol showed significant increase in UI, while preadministration of tBHQ at both the doses showed significant reduction in UI. Ismail et al reported that administration of ethanol produced linear haemorrhagic lesions, extensive submucosal oedema, mucosal friability, inflammatory cells infiltration and epithelial cell loss into the gastric lumen.…”
Section: Discussionmentioning
confidence: 85%
“…The data of the current study showed an upregulation of gene expression of proinflammatory cytokines: TNF- α and IL-1 β in the gastric mucosa of the EtOH-treated rats. In the same context, Katary and Salahuddin [ 44 ] reported the enhancement of gene expression and mucosal levels of TNF- α along with increased mucosal levels of IL-1 β after ethanol consumption in rats. The gastric inflammatory condition has been associated with the release of TNF- α , which activates the immune cells and other proinflammatory cytokines and increases the NF- κ B expression [ 45 ].…”
Section: Discussionmentioning
confidence: 97%